Exploring dimensions of health literacy: a case study of interventions to promote and support breastfeeding - Gillis, Doris E. (2009)
At a time when health literacy is emerging as a central concern in the health field, this thesis examines whether and how practitioners involved in the promotion of breastfeeding incorporate dimensions of health literacy as described in the current literature. Although there is little evidence that practitioners are familiar with specific definitions of health literacy, their description of practices reflected various facets of health literacy including functional health literacy, interactive and critical health literacy, and health literacy as composed of multiple literacies.